Food parenting and health status of malnutrition toodlers in Kendari, 2015 : A qualitative study - Gusti Ayu Putu Reskiyanti; Hartati Bahar; Hariati Lestari (CORE JOURNAL, 2020)
Insufficient food and health parenting for children has the most important role that causes malnourished problem. The prevalence of malnutrition in working area of Puskesmas Mekar (Public Health Center) reached 26,3% in 2013, and decreased to be 10,5% in 2014. The purpose of the research is to do an in-depth analysis on food and health parenting for the under-five children with malnutrition in working area of Puskesmas Mekar of Kendari Municipality. This is a qualitative research that uses phenomenological approach. The informants were chosen by using purposive sampling technique. The result of the research showed that the food and health parenting for the under-five children with malnutrition in working area of Puskesmas Mekar I n the case of food type provided for children were generally breast milk, rice with side dishes, and porridge. The feeding schedule is in the morning, in the afternoon, and in the evening, while the feeding frequency is 2-4 times in a day, however it is usually done with uncertain time. The feeding technique is conducted differently depends on the nursemaid. For the situation when feeding, the nursemaid commonly feeds the children while walking and watching TV. Not only the nursemaid feeds the children but also family like grandmother, father, and sister. Puskesmas usually solves the malnutrition problem by providing milk and special porridge, monitoring the body weight of children, and administering training for the nursemaid. While the health parenting for the under-five children with malnutrition in working area of Puskesmas Mekar, for sleeping schedule, the children usually sleep at two golden time namely day time and night time; the monitoring to children when playing is conducted by both the nursemaid and her family. For seeking medicine, the nursemaid usually gives traditional treatment at home such as giving febrifuge, and compressing. For health and environmental sanitation, washing hands habit done by the nursemaid is good enough. The health officers give special treatment to the malnourished children by providing them milk and special porridge, monitoring the body weight of children, and administering training for the nursemaids